Ab initio calculation of the adsorption of As, Cd, Cr, and Hg heavy metal atoms onto the illite(001) surface: Implications for soil pollution and reclamation. (1st November 2022) - Qi, Chongchong; Xu, Xinhang; Chen, Qiusong; Liu, Hui; Min, Xiaobo; Fourie, Andy; Chai, Liyuan
Abstract: Elucidating the mechanisms of heavy metal (HM) adsorption on clay minerals is key to solving HM pollution in soil. In this study, the adsorption of four HM atoms (As, Cd, Cr, and Hg) on the illite(001) surface was investigated using density functional theory calculations. Different adsorption configurations were investigated and the electronic properties (i.e., adsorption energy (Ead ) and electron transfer) were analyzed. The Ead values of the four HM atoms on the illite(001) surface were found to be As > Cr > Cd > Hg. The Ead values for the most stable adsorption configurations of As, Cr, Cd, and Hg were −1.8554, −0.7982, −0.3358, and −0.2678 eV, respectively. The As atoms show effective chemisorption at all six adsorption sites, while Cd, Cr, and Hg atoms mainly exhibited physisorption. The hollow and top (O) sites were more favorable than the top (K) sites for the adsorption of HM atoms. The Gibbs free energy results show that the illite(001) surface was energetically favorable for the adsorption of As and Cr atoms under the influence of 298 K and 1 atm. After adsorption, there was a redistribution of positions and reconfiguration of the chemical bonding of the surface atoms, with a non-negligible influence around the upper surface atoms. Bader charge analysis shows electrons were transferred from the surface to the HM atoms, and a strong correlation between the valence electron variations and the adsorption energy was observed. HM atoms had a high electronic state overlap with the surface O atoms near the Fermi energy level, indicating that the surface O atoms, though not the topmost atoms around the surface, significantly influence HM adsorption. The above results show illite(001) preferentially adsorbed As among all four investigated HM atoms, indicating that soils containing a high proportion of illite might be more prone to As pollution. Graphical abstract: Image 1 Highlights: The adsorption of four HM atoms on the illite(001) was investigated by DFT. The Ead of HM atoms on the illite(001) were ranked as: As > Cd > Cr > Hg. The correlation between valence electron variations and Ead was analyzed. The adsorption phenomena of heavy metal atoms were investigated by the PDOS.